E-deltagelse i praksis: Politikernes og forvaltningens medkonstruktion og konsekvenserne heraf - Christine Secher (Copenhagen Business School (CBS), 2010)
– This thesis is about how different e-participation user groups co-construct technology through the use in practice. It is studied how technology is used on a municipality level for citizen-communication and -participation with an online debate forum as a case in point. Users of online debates are citizens, politicians and the administration. In this thesis, I have chosen to focus on how politicians and the administration use online debates. I show how politicians and the administration participate in very distinct ways on the debate forum and thereby create specific forms of citizen communication and participation. Everybody can participate in the online debate as long as they give up their name and email. Periodically, citizens write quite a lot of contributions on the debate forum. But politicians' and the administration's perception of what is happening on the debate influence which role the citizens's contributions will have for the politicians and administration, as well as forms of interaction between users. In this thesis, I argue that the users' (politicians's and administration's) sensemaking about online debates as well as the mediation of the use of online debates have a crucial influence on which types of practice of online debate can develop. Online debate is perceived as an equivocal technology in the sense that the use of the technology is not clear cut but a result of the user's sensemaking about the technology and thereby the sensemaking about possible acts and interactions with the technology and other users. Sensemaking is the primary theoretical frame with a special focus on situation-specific cue-frame-relations. The Municipality of Odder is the case and a unique one with its 11 years of experience within municipally facilitated online debate. The empirical data are contributions written from September 3rd, 2005 to April 15, 2008 (a total of 1983 contributions), 17 semi-structured interviews of -1 hours length with administration and politicians in the municipality as well as different written documents from the municipality. In this thesis I show that politicians and administration act as users of the online debate in four different ways: Political candidate, councilor, administrator and mediator. The political candidate run for the municipal election and is only present in the debate the last three months before the election. The political candidate see online debates as a good opportunity to make him/herself visible to voters and competing candidates, and therefore (s)he writes a lot of contributions during this period. The political candidate rarely answers ordinary citizen's contributions but instead decides to write new contributions or answer contributions started by competitors. The political candidate rarely gets involved in real discussions on the debate but instead choose to give his/her visions for the future of the Municipality of Odder. The councilor see the debate as the citizen's opportunity to voice their meaning and therefore rarely participate in the debate, as this could have a negative effect on citizens motivation to write on the debate. The councilor reads the citizens' contributions and once in a while the contributions act as input for internal council discussions. When the contribution reflect misunderstanding and when it is not only a few citizens who share the misunderstanding, the councilor chooses to write a report for the debate. It is usually the relevant committee chairman or equivalent who writes the contribution. The administrator believes that the majority of the contributions on the debate are political and therefore (s)he should not participate in the debate. The administrator sees citizens and business as partners. It is groups of professionals, which cover associations, organizations etc. and does not necessarily, see the individual citizen as a key stakeholder. The groups of professionals use other media, such as mails and letters, in their communication with the administration, as their input is often long reports and technical judgments. The administrator chooses only to answer factual misunderstandings in ongoing processes or more general issues in the municipality. The mediator, which is a role only a small part of the administration acts in, generally works with the implementing and forming the use of technology in the municipality. (S)he sees ICT as a way of increasing openness and effectiveness in the municipality. Online debates is a solution which the mediator believes especially increases openness and (s)he works with the aim of ensuring a continued debate. The mediator focuses on maximizing the number of contributions, on making it easy to participate and to make it possible to discuss anything, which is why the debate is in no editor or guided use of the debate. The result is that the individual user – political candidate, councilor and administrator – mediate the use of the debate and develop filters for their own and others' ability to act on the online debate. That politicians and administration appear in these four roles in relation to online debate problematic several aspects of the use of e-participation practices in a municipal context. One aspect is that the four roles develop different practices for the use of the debate which function parallel on the debate without the development of a common practice. A second aspect is that a mediator role is established. An actor who mediates the interaction between citizen and politician, and thereby an actor who has a high degree of importance for what online debating becomes in practice. A third aspect is that the administration takes the mediating role and becomes a political advisor or an administrator of political decisions. A shift which neither the politicians nor the administrator are aware of. At the same time, the way the technology is mediated creates both synergy and conflict between the councilor, the political candidate and the administrator. Synergy and conflict which primarily can be related to the focus of the mediator on the increased use of the technology and the missing focus on contextualization of the online debate.
hdl:10398/8000
Keywords: 650